2001
DOI: 10.1093/carcin/22.9.1421
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of phorbol ester-induced AP-1-DNA binding, c-Jun protein and c-jun mRNA by dietary energy restriction is reversed by adrenalectomy in SENCAR mouse epidermis

Abstract: The aim of this study was to determine the effects of 40% dietary energy restriction (DER) relative to ad libitum feeding on AP-1-DNA binding and expression of c-Jun protein and c-jun mRNA in SENCAR mouse skin treated with acetone or 12-O-tetradecanoylphorbol 13-acetate (TPA). The role of the glucocorticoid hormone corticosterone (CCS) was investigated by adding CCS or vehicle control to the drinking water of adrenalectomized mice. AP-1-DNA binding, measured by electrophoretic mobility shift assay, showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 24 publications
3
23
0
1
Order By: Relevance
“…Briefly, TPA activates PKC-Raf-MAPK signal transduction pathways and then promotes proliferation. Previous studies have demonstrated that DCR inhibited skin carcinogenesis by suppressing TPAinduced AP-1 transcriptional activation via blocking PKC-Raf-ERK signal (32)(33)(34). Our current data provide significant novel information that the reduction of circulating IGF-1 levels may induce an abrogated IGF-1-dependent signaling, and thereby co-inhibit TPA-induced cancer promotion.…”
Section: Accession Numbersupporting
confidence: 51%
See 1 more Smart Citation
“…Briefly, TPA activates PKC-Raf-MAPK signal transduction pathways and then promotes proliferation. Previous studies have demonstrated that DCR inhibited skin carcinogenesis by suppressing TPAinduced AP-1 transcriptional activation via blocking PKC-Raf-ERK signal (32)(33)(34). Our current data provide significant novel information that the reduction of circulating IGF-1 levels may induce an abrogated IGF-1-dependent signaling, and thereby co-inhibit TPA-induced cancer promotion.…”
Section: Accession Numbersupporting
confidence: 51%
“…Activated GTP-bound Ras further initiates the MAPK cascade. Previous studies demonstrated that DCR treatment inhibited TPA-promoted skin carcinogenesis by reducing certain isoforms of PKC (32) down to the ERK pathway (33), and then repressing transcriptional regulation of AP-1 (34).…”
mentioning
confidence: 99%
“…Because TPA is a well known AP1 activator (15,16), we examined the effects of TPA on BCSG1 promoter activity. Treatment of cells with TPA for 24 h stimulated the BCSG1 promoter activity 3.1-fold in SKBR-3 cells, 2.3-fold in T47D, and 4.9-fold in HepG2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies are needed to elucidate whether the binding of SIRT1 to bZIP domain of c-Fos and c-Jun participates in AP-1 transcriptional regulation in a deacetylase-independent manner. CR decreases AP-1 DNA binding in mouse epidermis (43) and attenuates the aging-related AP-1 activation (23,44). Numerous studies have linked the beneficial effects of mammalian CR with increased cellular SIRT1 expression (18,26).…”
Section: Sirt1 Is a Nadmentioning
confidence: 99%